PENGEMBANGAN MULTIMEDIA INTERAKTIF UNTUK PEBELAJARAN VOLUME BANGUN RUANG DI KELAS V SEKOLAH DASAR - Dina Arina; Endang Sri Mujiwati; Ita Kurnia (Prima Magistra: Jurnal Ilmiah Kependidikan, 2020)
Students' understanding of the volume geometry is still not enough. This is because the teacher only explains the material on the volume of space with the blackboard media. The media is less interactive for learning the material of the volume of geometrical space so that the concept of volume of geometric space cannot be understood by students optimally. The purpose of this development research is to describe the validity of interactive multimedia-based media to explain and determine the volume of 5th grade student room building. The development model used in this study is the ADDIE model. The procedure of the ADDIE model consists of 5 stages, but this study only uses four stages. The stages carried out in this study did not go through the implementation stage because of the existence of Covid-19 so that it did not support the implementation of the learning program by applying the learning media that had been made. Data collection techniques in this study were to conduct observations, interviews, and questionnaires. The data analysis technique used is the validity criteria. From the results of media validation and material in interactive multimedia, the values were 97.6% and 96%. Thus interactive multimedia for the volume of 5th grade building materials at SDN Damarwulan IV was declared to be very valid and could be used without the need for improvement.